2004
DOI: 10.1111/j.1432-1033.2004.04009.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic approaches to the cellular functions of polyamines in mammals

Abstract: The polyamines putrescine, spermidine and spermine are organic cations shown to participate in a bewildering number of cellular reactions, yet their exact functions in intermediary metabolism and specific interactions with cellular components remain largely elusive. Pharmacological interventions have demonstrated convincingly that a steady supply of these compounds is a prerequisite for cell proliferation to occur. The last decade has witnessed the appearance of a substantial number of studies, in which geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
148
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 157 publications
(261 reference statements)
4
148
0
Order By: Relevance
“…While Kaul et al and Chaux et al demonstrated efficacy with periadventital delivery of SPER/NO, SPER/NO dissociates into NO and spermine, the latter of which has biologically active properties that may not be beneficial to the vasculature. [23,25,39] Despite the significant efficacy of our therapies, some limitations exist. Most polymers, despite the rapid improvements in their safety profile, still carry some adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…While Kaul et al and Chaux et al demonstrated efficacy with periadventital delivery of SPER/NO, SPER/NO dissociates into NO and spermine, the latter of which has biologically active properties that may not be beneficial to the vasculature. [23,25,39] Despite the significant efficacy of our therapies, some limitations exist. Most polymers, despite the rapid improvements in their safety profile, still carry some adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Due to enzyme immaturity of the neonatal small intestine the fraction of ingested proteins reaching the colon, and the subsequent availability as substrate to be metabolised by colonic microbiota, may be even higher in infancy (34) . Increasing protein intake enhanced the faecal concentration of bacterial metabolites arising from putrefaction (ammonia, phenol compounds or polyamines) which are thought to have deleterious effects, except for polyamines which have been shown to be beneficial for epithelial cell proliferation (35) .…”
Section: Effects Of Nutritional Programming On the Gastrointestinal Tmentioning
confidence: 99%
“…These results were consistent with that in screening experiment. Putrescine is one of the polyamines which are cellular constituents shown to be essential for a variety of cell processes related to growth and differentiation, such as DNA replication, transcription and translation (Janne et al 2004). It has been widely utilized as an additive in the development in serum-free media and various literature references have reported its prominent effect on cell growth and protein expression (Jeon et al 2010;Kim et al 2006).…”
Section: Discussionmentioning
confidence: 99%